2018
DOI: 10.1101/505776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining the link between alpha-gal-containing antigens in North American ticks and red meat allergy

Abstract: Development of specific IgE antibodies to the oligosaccharide galactose-α-1, 3galactose (α-gal) following tick bites has been shown to be the source of red meat allergy. In this study, we investigated the presence of α -gal in four tick species: the lonestar tick (Amblyomma americanum), the Gulf-Coast tick (Amblyomma maculatum), the American dog tick (Dermacentor variabilis), and the black-legged tick (Ixodes scapularis) by using a combination of immunoproteome, carbohydrate analysis, and basophil activation a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The hIgE mAb to alpha-gal will enable better diagnostic tests for alpha-gal to be developed. Investigations of the immunopathogenesis of red meat allergy, including the presence of alpha-gal in the tick saliva and the role of alpha-gal in coronary artery disease, will also be facilitated (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The hIgE mAb to alpha-gal will enable better diagnostic tests for alpha-gal to be developed. Investigations of the immunopathogenesis of red meat allergy, including the presence of alpha-gal in the tick saliva and the role of alpha-gal in coronary artery disease, will also be facilitated (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al ( 129 ), however, detected the presence of α-Gal epitopes in the midgut, hemolymph and salivary glands of I. ricinus females regardless of their feeding status. Meanwhile, three genes involved in the synthesis of α-Gal have been identified in I. scapularis genome ( 80 ) and the presence of α-Gal has also been confirmed in Amblyomma americanum ticks fed on human blood, which lacks α-Gal ( 130 ). All these findings support the view that α-Gal moieties present in tick tissues and saliva do not originate from a prior blood meal but are produced by the ticks themselves.…”
Section: Sensitization To α-Galmentioning
confidence: 99%
“…Sensitization may be induced by ticks via the presence of mammalian blood in the tick midgut after a blood meal (12), the presence of endogenous tick alpha-gal antigens (including those found in non-fed larval ticks) (13) or alpha-gal producing tick-borne microbial pathogens (14). Recent studies have shown alphagal epitopes in the salivary glands of fed Amblyomma americanum and Ixodes scapularis (15), Ixodes. ricinus (9) and Haemaphysalis longicornis (16) and the mid-guts of ticks belonging to the Ixodes family, particularly I. ricinus (12) and I. scapularis (15).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown alphagal epitopes in the salivary glands of fed Amblyomma americanum and Ixodes scapularis (15), Ixodes. ricinus (9) and Haemaphysalis longicornis (16) and the mid-guts of ticks belonging to the Ixodes family, particularly I. ricinus (12) and I. scapularis (15). However, other organisms have not been rigorously examined for the presence of alpha-gal or their ability to induce IgE responses against alpha-gal.…”
Section: Introductionmentioning
confidence: 99%